Two New Species of Neolitsea (Lauraceae), N. kraduengensis from Thailand and N. vuquangensis from Vietnam and an Analysis of their Phylogenetic Positions using ITS sequences - Mitsuyuki, Chika (The Japanese Society for Plant Systematics, 2023)
Two novel species of eolitsea (Lauraceae), eolitsea aduen ensis Tagane & Yahara and . u uanensis Mitsuyuki & Yahara, are described and illustrated. eolitsea aduen ensis occurs in Phu Kradueng National Park, Loei Province, Northeast Thailand. eolitsea u uan ensis is in Vu uang National Park, Ha Tinh Province, North Central Vietnam. Morphological differences of the two species from similar species are presented. A phylogenetic tree reconstructed from ITS sequences supports their distinctiveness. Two phenotypically similar species, eolitsea au ata and . u uan ensis, with dense golden yellow hairs on the leaf blades, are not sister to each other.